Resilience, robustness and adaptivity: Large urban Russian Federation regions during the COVID-19 crisis - Turgel, Irina D.; Chernova, Olga A.; Usoltceva, Anastasiia A. (Area development and policy, 2022)
An analysis of the response of highly urbanized Russian regions to the onset of the Covid-19 pandemic shows that regions with a high urban population share and many small and medium-sized businesses were most vulnerable; that regional differences were largely determined by the severity of health-related restrictions on business and social activity; and the extent to which regionally differentiated economic support measures and the adoption of digital technologies, new delivery methods, and a focus on new sectors stabilized aggregate supply and demand. Examination of the evolution of a resilience index permits identification of four paths: adaptively stable, vulnerable labile-adaptive, remission-adaptive and low-adaptive economies, and it reinforces the interpretation of the main drivers of regional resilience.